PERAN PEMERINTAHAN DESA DALAM PENGELOLAAN KEUANGAN DESA ALAI KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI TAHUN 2012 - Muhammad Basirruddin; Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Village in one form small community ,which is a small group of sedentary life ina region that remains. In the PP 72 of 2005 concerning the organization of theaffairs of the village where the village administration under the authority of thevillage funded from Budget village and help the Government in accordance withthe Ministry of Home Affairs letter No : 140/640SJ dated March 22, 2005 on theVillage Fund Allocation Guidelines (ADD ) of the District Government toGovernment village. Through Allocation Fund Village, the village has anopportunity to manage the development, administration and social villageautonomously. At the Law No. 32 Year 2004 on Regional Government, assertsthat